Reframing EFL Speaking Performance: Why Psychological Readiness Outweighs Vocabulary Knowledge in Indonesian High School Learners - Darmawati; Muhammad Tahir; Andi Asrifan (Foreign Language Instruction Probe, 2026)
As communicative competency gains prominence in English language education, it has become crucial to comprehend why numerous learners continue to exhibit reluctance or ineffectiveness in oral contact despite extensive formal instruction in English as a Foreign Language courses. Previous research has mostly focused on linguistic ability, especially vocabulary acquisition, whereas comparatively less emphasis has been placed on the impact of psychological preparedness on speaking performance. This study examined the relative impact of self-confidence, self-efficacy, and vocabulary knowledge on the speaking performance of Indonesian senior high school students. A quantitative correlational design was utilized to gather data from 30 eleventh-grade students using self-confidence and self-efficacy questionnaires, a vocabulary knowledge test, and a monologue-based speaking assessment, followed by descriptive statistics, correlation analysis, and multiple linear regression techniques. The investigation indicated that self-confidence and self-efficacy had a substantial beneficial impact on speaking performance, while vocabulary knowledge exhibited a relatively weaker and statistically insignificant predictive capability inside the regression model. These findings indicate that oral communication in EFL environments is influenced not just by lexical resources but also by learners' psychological readiness to engage, persevere, and speak amid ambiguity. This study reinterprets speaking performance as a psychologically influenced process, contributing to broader discourses on communicative competence and emphasizing the significance of affective-oriented speaking pedagogy in modern language education.